Influence of wood sample size and species on the leaching of chromium and copper using different lab tests - Bahmani, Mohsen; Schmidt, Olaf; Fromm, Jörg; Melcher, Eckhard (Maderas. Ciencia y Tecnología, 2016)
The present study deals with the development of standardized laboratory methods to predict depletion of biocides more accurately under service condition. Laboratory test was conducted with EN 252 standard and non-standard pine as well as spruce specimens to determine leaching of chromium and copper from stakes pressure impregnated with commercial copper- and chromium-containing preservative. Two modified laboratory test methods were carried out; first discontinuous (CEN/TS 15119-1) and second continuous water immersion (CEN/TS 15119-2). Results showed that leaching of copper in pine sapwood specimens was higher than that in spruce specimens. Moreover, copper leaching was greater in comparison to leaching chromium.